PARENTING BEHAVIOUR AND STUNTING PREVENTION IN SOUTH SULAWESI PROVINCE, INDONESIA - Azis, Rahmawati; Rahayu, Irma; Alif, Adimas Buyar; Samsidarwati, Besse; Akmal, Akmal; Masriadi, Masriadi (Jurnal Biometrika dan Kependudukan, 2025)
Stunting in children is influenced not only by food availability but also by various factors such as family caregiving practices, which in many cases remain suboptimal. There are still families who have not practiced optimal parenting patterns. This study aims to determine family parenting behavior and analyze factors that can support increased efforts to prevent stunting in toddlers. The study used a quantitative approach with a survey method, the population was all families with toddlers in South Sulawesi Province and 260 families as samples. The data were processed and analyzed through three stages: univariate analysis to describe the characteristics of the variables, bivariate analysis using the Chi-square statistical test (with Yates’ correction) to see the relationship between variables, and multivariate analysis using a binary logistic regression model. The study's results showed a positive relationship between parenting behavior and parenting knowledge, environmental sanitation knowledge, nutritional knowledge, parenting attitudes, parenting motivation, family planning, and culture  (p<0.05). Meanwhile, the variables of environmental health knowledge and environmental sanitation attitudes did not show a significant relationship (p>0.05). The main strategies for interventions to improve family parenting behavior in efforts to prevent stunting are culture (B=2.492;p=0.000), environmental sanitation knowledge (B=1.936;p=0.000), family planning (B=1.429;p=0.030), and parenting attitudes (B=1.003;p=0.000). Recommendations include involving local stakeholders, including community leaders, religious leaders, and regional organizations in supporting family parenting efforts in controlling stunting through increasing environmental sanitation knowledge, family planning, and positive parenting attitudes based on local wisdom.